Disease Burden of Chronic Hepatitis B among Immigrants in Canada - William WL Wong; Gloria Woo; E Jenny Heathcote; Murray Krahn (Canadian Journal of Gastroenterology)
BACKGROUND: The prevalence of chronic hepatitis B (CHB) infection among immigrants to North America ranges from 2% to 15%, 40% of whom develop advanced liver disease. Screening for hepatitis B surface antigen is not recommended for immigrants.